(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Its poor quality was one of the key problems preventing recycled course aggregate (RCA) from being used in concrete mixes. The quality of recycled aggregate may be impacted by cement mortar on the surface of the material. The examination of recycled aggregate in various test results employing acid soaking treatment procedures utilizing sulfuric acid and phosphoric acid is the subject of this research. Natural aggregate, recycled aggregate, recycled aggregate with H2SO4 and recycled aggregate with H3PO4 are the four types of concrete mixtures that are made. Using these cleaned recycled aggregates in concrete has been proven to be beneficial. The strength and durability of concrete were also evaluated, and aggregate attributes were computed. The test findings showed. The behavior of recycled aggregate has changed according to the test results after being treated with acid. Out of these two acids, sulphuric acid treatment of recycled aggregates produced the best results, followed by phosphoric acid doing only marginally better. According to the overall research, employing treated recycled aggregate in concrete can significantly increase the strength and durability properties of concrete made using recycled aggregate.